Efecto de Trichoderma spp. Y Bacillus spp. en el crecimiento y rendimiento del cultivo de maní (Arachis hypogaea) variedad INIAP 382 - Farias Cedeño, Karla Lorena (2024)
This research was developed with the aim of evaluating the effect of Trichoderma spp. and Bacillus spp. on the growth and yield of the peanut crop (Arachis hipogaea) variety INIAP 382; for which seven treatments based on microorganisms were used with different application frequencies: Trichoderma / 8 days (T1), Trichoderma / 15 days (T2), Bacillus / 8 days (T3), Bacillus / 15 days (T4), Trichoderma x Bacillus / 8 days (T5), Trichoderma x Bacillus / 15 days (T6) and the control. A Completely Randomized Block Design was used, with 4 replications. The best yields were achieved by applying Trichoderma alone and in combination with Bacillus in treatments T1, T2, T3, T4 and T5 compared to the control in the variables number of branches, number of grains per pod, weight of 100 grains (g) and yield kg ha-1, while for the variables plant height and number of pods there are no differences. Therefore, the use of both microorganisms alone and in combination allows to increase values in certain productive variables of peanut cultivation.